Pengaruh stimulus terhadap pembelian impulsif melalui reaksi kognitif dan afektif: Kerangka kerja Stimulus-Organism-Response (SOR) - Intan Rahmawati; Feri Setyowibowo (Universitas Negeri Surabaya, 2025)
This study aims to examine the indirect effect of various stimuli on impulsive buying through two mediating paths, namely cognitive reactions (financial literacy) and affective reactions (shopping enjoyment). This research expands understanding in the realm of impulsive buying-related studies by integrating various types of stimuli and comparing the role of cognitive and affective reactions, which are still rarely studied simultaneously in the study of college students' online shopping. Purposive sampling was used to select 155 university students in Surakarta as the research sample. Quantitative methodology based on Partial Least Square-Structural Equation Modeling (PLS-SEM) path analysis was used. The results showed that the affective mediation path (shopping enjoyment) significantly mediated the effect of stimulus on impulsive buying, however, there was no significant impact of cognitive mediation (financial literacy). This finding indicates that impulse buying behaviour tends to be triggered more by emotional aspects than by rational considerations. The practical implication is the importance of creating an emotionally pleasurable shopping experience. This research also opens up opportunities for further studies by exploring other variables to explain impulsive buying behaviour more comprehensively.